2014
DOI: 10.1109/jphotov.2013.2294755
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Parameterization of Carrier Mobility Sum in Silicon as a Function of Doping, Temperature and Injection Level

Abstract: Abstract-Based on contactless photoconductance measurements of silicon wafers, we have determined the sum of the electron and hole mobilities as a function of doping, excess carrier concentration, and temperature. By separately analyzing those three functional dependences, we then develop a simple mathematical expression to describe the mobility sum as a function of carrier injection wafer doping and temperature from 150 to 450 K. This new parameterization also provides experimental validation to Klaassen's an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…From our results, we can conclude that the Klaassen model offers a better description of the experimental data retrieved by TRTS. A conclusion that agrees with non-contact PCD data collected over a narrower injection level window [9,13,29,30]. At present we cannot rationalize the slight deviation between TRTS data and those retrieved by contact methods for concentrations above 1•10 16 cm -3 , in this respect, Klassen suggests that this data might be underestimated by an increase of temperature in the system during the measurements [6].…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…From our results, we can conclude that the Klaassen model offers a better description of the experimental data retrieved by TRTS. A conclusion that agrees with non-contact PCD data collected over a narrower injection level window [9,13,29,30]. At present we cannot rationalize the slight deviation between TRTS data and those retrieved by contact methods for concentrations above 1•10 16 cm -3 , in this respect, Klassen suggests that this data might be underestimated by an increase of temperature in the system during the measurements [6].…”
Section: Resultssupporting
confidence: 57%
“…We are only aware of a couple of PCD works that have previously attempted such study. In these works they found that Klaassen model failed to describe the experimentally resolved trend for temperatures below ~150 K [9,29]. The reason for this disagreement is unclear to us, however, we note that for low temperatures, one should consider an extra effect decreasing charge carrier density in silicon, an effect linked to the condensation of photogenerated e-h pairs into excitons.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…It can be observed that, as the temperature increased, the sensitivity of the sensor decreased, while the zero-output increased (for the convenience of comparison, this paper regards the output of the pressure sensor as the zero output at 2 bar). This is because the carrier mobility of silicon decreases with the increasing temperature; thus, the piezoresistive coefficient of the sensor decreases [ 31 ], resulting in a decrease in the sensor sensitivity. The ideal sensor chip has a uniform doping concentration and four identical resistors (R1 = R2 = R3 = R4).…”
Section: Resultsmentioning
confidence: 99%